Music in Natalya Nesterova’s Painting - Krivitskaya Evgeniya (Художественная культура)
The article discusses the friendship and creative connections between the famous representatives of Russian culture — painter Natalya Nesterova and composer David Krivitsky. The relevance of the topic is connected with Nesterova’s 80th birthday anniversary the world is celebrating. This is a reason to draw attention to the fact that at the moment there is an extremely limited number of scientific works devoted to her heritage. This article for the first time publishes some unknown facts from her artist’s biography and presents her pictures from the composer’s personal archive. The research perspective is to reveal the significance of musical art and performance for N.I. Nesterova and to show the originality of her approach to depicting musicians and the intended symbolic meaning in her paintings with musical subjects. As an exceptional case, the article describes her activities as an illustrator for the music editions of the composer D.I. Krivitsky. It can be concluded that communication between the two bright creative personalities had a mutual influence and served as an impetus for the emergence of interesting works of art.